Effects of Pancreatitis and Type 2 Diabetes Mellitus on the Development of Pancreatic Cancer: A Nationwide Nested Case-Control Study - Young-eun Kim; Min Heui Yu; Chung Mo Nam; Eun Seok Kang (Diabetes & Metabolism Journal)
Background Despite diabetes mellitus (DM) and pancreatitis being known risk factors for pancreatic cancer, patients with these conditions are not included in pancreatic cancer screening due to the low incidence of pancreatic cancer in these populations. This study aimed to determine the high-risk subgroup of patients with diabetes and pancreatitis that would benefit from pancreatic cancer screening. Methods A nested case-control study was conducted using data from the National Health Information Database of the Korean National Health Insurance Service. Patients were categorized into the following groups: type 2 diabetes mellitus only (T2DM-only), pancreatitis-only (PAN-only), T2DM followed by pancreatitis (T2DM-PAN), post-pancreatitis diabetes mellitus (PPDM), and no diabetes and no pancreatitis (NDNP). Conditional logistic regression was used to determine significant associations of each group with pancreatic cancer development risk. Results The risk of pancreatic cancer was significantly higher in the T2DM-PAN (adjusted odds ratio [AOR], 4.96; 95% confidence interval [CI], 4.48 to 5.49) and PPDM (AOR, 4.71; 95% CI, 4.12 to 5.37) groups than in the NDNP group. Compared to patients in the NDNP group, those with PPDM using insulin had a 17-fold increased risk (AOR, 16.72; 95% CI, 9.50 to 29.43), and individuals with PPDM who had diabetes for less than 3 years had a more than 8-fold increased risk of pancreatic cancer (AOR, 8.83; 95% CI, 5.99 to 13.01). Conclusion In patients with post-pancreatitis diabetes, insulin use or shorter duration of diabetes was associated with a higher risk of pancreatic cancer, suggesting that patients in these subgroups may require close monitoring for pancreatic cancer development.